Enhancing intestinal anastomotic healing using butyrate: Systematic review and meta-analysis of experimental animal studies. - Aurelia C L Wildeboer; Claire P M van Helsdingen; Camille G Gallé; Rob B M de Vries; Joep P M Derikx; Nicole D Bouvy (PLoS ONE, 2023)
Background Despite advancements in surgical technique and perioperative care, intestinal anastomoses still have a 10-15 per cent risk of leakage, which results in considerable morbidity and/or mortality. Recent animal studies have suggested that administration of butyrate to the anastomotic site results in enhanced anastomotic strength, which may prevent leakage. This systematic review and meta-analysis summarises current evidence concerning the effect of butyrate administration on anastomotic healing and will form a scientific basis for the development of new research into this subject. Methods Animal studies on the effect of butyrate-based interventions in models of intestinal anastomotic healing were systematically retrieved from online databases. Bibliographical data, study characteristics and outcome data were extracted, and internal validity of the studies was assessed. Outcomes studied through meta-analysis concerned: anastomotic strength, anastomotic leakage, collagen metabolism and general histologic parameters of wound healing. Results A comprehensive search and selection identified 19 relevant studies containing 41 individual comparisons. Design and conduct of most experiments were poorly reported resulting in an unclear risk of bias. Meta-analyses showed that butyrate administration significantly increases anastomotic strength (SMD 1.24, 0.88 to 1.61), collagen synthesis (SMD 1.44, 0.72 to 2.15) and collagen maturation, making anastomoses less prone to leakage in the early postoperative period (OR 0.37, 0.15 to 0.93). Conclusion This systematic review and meta-analysis shows that there is potential ground to investigate the use of butyrate in clinical trials to prevent anastomotic leakage in intestinal surgery. However, more research is necessary to define the best application form, dosage and administration route.